2015
DOI: 10.1016/bs.ircmb.2015.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Biology of the Pentraxin Protein Family: Evolutionarily Conserved Component of Innate Immune System

Abstract: Abstract.In addition to its roles in hemostasis and wound repair, the blood clot plays an underappreciated role in innate immunity, where the established clot serves as a barrier to microbial penetration into the internal milieu and where the early clot entraps and immobilizes microbes that have entered wounds to the integuments. In this report we document the behavior of the pathogenic gram-negative bacterium Vibrio harveyi that has been entrapped in the fabric of the extracellular blood clot of one of its ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 142 publications
0
22
0
Order By: Relevance
“…CRP, together with serum-amyloid P component (SAP), shape the former one 3 . Human CRP and SAP show high degrees of sequence identity (51%) 7 , analogous molecular structures and functions 6,8,9 and overlapping ligand specificities 10,11 . Therefore, it is not surprising that short pentraxins show species-specific, strain-specific, gender-specific (i.e., hormonal-specific), and interchangeable acute phase reactivity 2,[12][13][14][15][16] .…”
Section: Zebrafish C-reactive Protein Isoforms Inhibit Svcv Replicatimentioning
confidence: 99%
See 1 more Smart Citation
“…CRP, together with serum-amyloid P component (SAP), shape the former one 3 . Human CRP and SAP show high degrees of sequence identity (51%) 7 , analogous molecular structures and functions 6,8,9 and overlapping ligand specificities 10,11 . Therefore, it is not surprising that short pentraxins show species-specific, strain-specific, gender-specific (i.e., hormonal-specific), and interchangeable acute phase reactivity 2,[12][13][14][15][16] .…”
Section: Zebrafish C-reactive Protein Isoforms Inhibit Svcv Replicatimentioning
confidence: 99%
“…The polarized planar structure of the circulating CRP molecules with opposite ligand recognition and multifunctional effector faces defines the CRP as soluble pattern recognition receptors endowed with crucial innate immune activities 1,10 . It has been extensively reported that the human pentameric CRP can recognize and bind, in a Ca 2+ -dependent manner, the surface-exposed phospholipid heads, preferentially phosphorylcholine 17 .…”
Section: Zebrafish C-reactive Protein Isoforms Inhibit Svcv Replicatimentioning
confidence: 99%
“…Pentraxins are lectins which play important roles in the innate immune response by recognizing and binding to specific carbohydrate moieties on the surface of microorganisms. Carbohydrate binding facilitates agglutination, complement‐mediated opsonization, cell lysis and a range of other cellular processes (Armstrong, ). However, only a few studies have reported the response of pentraxin to environmental stress; thus, its participation in oyster stress responses is poorly understood (Armstrong, ; Olafsen, ).…”
Section: Discussionmentioning
confidence: 99%
“…Carbohydrate binding facilitates agglutination, complement‐mediated opsonization, cell lysis and a range of other cellular processes (Armstrong, ). However, only a few studies have reported the response of pentraxin to environmental stress; thus, its participation in oyster stress responses is poorly understood (Armstrong, ; Olafsen, ). Another differentially expressed lectin identified in the current study, perlucin, is involved in nucleation of calcium carbonate ions during shell formation (Blank et al., ; Mann, Weiss, André, Gabius, & Fritz, ; Weiss, Kaufmann, Mann, & Fritz, ).…”
Section: Discussionmentioning
confidence: 99%
“…The methods reported in this paper to purify CRP apply only to human pentameric CRP. The methods to purify monomeric CRP and CRP from animals, such as fish and Limulus, may require different or additional steps for their purification (Armstrong, 2015;Elvitigala et al, 2015;Huong Giang et al, 2010;Li et al, 2013;Mattecka et al, 2013;Mihlan et al, 2011;Pathak et al, 2016;Pepys et al, 1982;Potempa et al, 2015;Singh et al, 2009;Suresh et al, 2004).…”
Section: Discussionmentioning
confidence: 99%